(untitled) (Advancements in Homeopathic Research, 2023)
Introduction: Arthritis is a term used for tenderness in the joints with swelling. It can affect one or more joints and is a gradually progressive disease which is not usually noticed in the early stages. WHO in its recent report states that musculoskeletal disorders are one of the disability causing disorders in the recent era which needs immediate and emergency care. Osteoarthritis (OA) and Rheumatoid arthritis (RA) are the common forms of arthritis presented in most of the peoples, and Fibromyalgia (FM) is a condition known as chronic pain syndrome affects 2% of population. Homoeopathy is a system which is can remove the sufferings permanently when administered constitutionally by exact similar remedy, potency and dose with frequent repetitions.Materials and Methods: A retrospective analysis had been done with 535 patients who had visited general OPD 2 at NHRIMH, Kottayam with rheumatological symptoms for about 1 year duration (between January 2022 to December 2022) to find out the frequently indicated medicines. Results: In this retrospective study among 535patients it had been observed that 32% (172) patients were between 51 and 60 age as maximum and 1% (2) patients were between 81-90 as minimum. Females were more affected than males. 57 (11%) old patients and 478 (89%) new patients had been noted during this study period. 22% (116) patients and had been diagnosed with Osteoarthritis (OA) as maximum and 4% (21) patients with fibromyalgia as minimum Sulphur 17%(87) and Rhustox 15% (78) had been prescribed in maximum patients and Iris versicularis in less patients2% (12). Conclusion: This retrospective study proves that all the rheumatologic diseases when treated with basic principles of homoeopathy and individualization, it is possible to make a permanent cure without side effects.